2019
DOI: 10.5713/ajas.18.0966
|View full text |Cite
|
Sign up to set email alerts
|

Effects of winter and spring housing on growth performance and blood metabolites of Pengbo semi-wool sheep in Tibet

Abstract: Objective Sixty Pengbo semi-wool sheep ewes (approximately 1.5-years-old; 31.33±0.43 kg) were randomly assigned to two groups, either grazing (G) or dry lot feeding (D), to examine the effects of traditional daily grazing and dry lot feeding on performance and blood metabolites during the cold season in Tibetan Plateau. Methods The ewes in the G group were grazed continuously each day and housed in one shed each evening, while the ewes in the D group were housed in anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Grazing through winter has always been problematic in China as temperatures are very low and modelling indicates that the energy costs of walking and grazing in winter greatly exceed the energy obtained from eating the dead plant material available (Zheng et al 2013;Jin et al 2019). One piece of evidence obtained for the desert steppe was that plant growth was significantly reduced in the year following heavy grazing pressure in winter, but more research is needed to identify the effects of intensity of grazing through winter on the subsequent state of various grassland types.…”
Section: Discussionmentioning
confidence: 99%
“…Grazing through winter has always been problematic in China as temperatures are very low and modelling indicates that the energy costs of walking and grazing in winter greatly exceed the energy obtained from eating the dead plant material available (Zheng et al 2013;Jin et al 2019). One piece of evidence obtained for the desert steppe was that plant growth was significantly reduced in the year following heavy grazing pressure in winter, but more research is needed to identify the effects of intensity of grazing through winter on the subsequent state of various grassland types.…”
Section: Discussionmentioning
confidence: 99%
“…The lower critical temperature of sheep is about −3 • C, depending on factors such as fleece length, wind speed, etc., and for every 1 • C drop from −3 • C, the daily maintenance metabolizable energy requirement of a 60 kg sheep increases by 0.14~0.64 MJ [22]. A previous study in a Tibetan winter found that the growth rate of ewes raised outdoors decreased by 28 g/d, compared with ewes raised in a shed [16]. Similarly, the ADG and feed efficiency of cattle has been reported to be lower in March, compared with a warmer April [2,3].…”
Section: Environmental Parameters Growth and Temperaturementioning
confidence: 95%
“…Keeping ewes in warm sheds during winter and spring can improve the lambing rate and the lambs' growth rates [15]. Compared to winter grazing, providing conserved feed indoors enhances their welfare, as evidenced by faster growth and better physiological and biochemical characteristics in the blood [16]. Oat hay is a suitable supplement to grazing in such conditions, as it can reverse a negative nitrogen balance and improve a sheep's energy status [17].…”
Section: Introductionmentioning
confidence: 99%
“…The N content of diets, fresh feces, and urine samples with sulfuric acid were measured according to the methods of Kjeldahl (AOAC, 2002, method 990.03). Superoxide dismutase (SOD), glutathione peroxidase (GSH‐Px), the content of malondialdehyde (MDA), and total antioxidant capacity (T‐AOC) were determined using a kit (Model 100T/96S, Suzhou Keming Biotechnology Co. Ltd.) and by spectrophotometry, on Microplate Reader (Model Epoch; Gene Company Limited) (Jin, Zhang, Badgery, Li, & Wu, 2019). Ruminal VFA was measured according to Capillary Gas Chromatography described by Luo et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, 10 g of the sample was dried in a microwave oven at 900W electric power for 2 min, and then electric power was adjusted to 600W to dry to a constant weight. DM of dried sample was determined according to the AOAC ( Company Limited) (Jin, Zhang, Badgery, Li, & Wu, 2019). Ruminal VFA was measured according to Capillary Gas Chromatography described by Luo et al (2015).…”
Section: Analytical Proceduresmentioning
confidence: 99%